Q. 14.4( 18 Votes )

# In each of the fo

Answer :

We have,

*f*(*x*) = *x*^{3}+4*x*^{2}-3*x*+10 and g (x) = x + 4

Therefore, by remainder theorem when f (x) is divided by g (x) = x – (-4), the remainder is equal to f (-4)

Now, *f*(*x*) = *x*^{3}+4*x*^{2}-3*x*+10

f (-4) = (-4)^{3} + 4 (-4)^{2} – 3 (-4) + 10

= -64 + 4 * 16 + 12 + 10

= 22

Hence, required remainder is 22.

Rate this question :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x^{31</s}RS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x^{3}RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics